2020
DOI: 10.1016/j.biomaterials.2019.119707
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in porphyrin-based nanocomposites for effective targeted imaging and therapy

Abstract: Porphyrins are organic compounds that continue to attract much theoretical interest, and have been called the "pigments of life". They have a wide role in photodynamic and sonodynamic therapy, along with uses in magnetic resonance, fluorescence and photoacoustic imaging. There is a vast range of porphyrins that have been isolated or designed, but few of them have real clinical applications. Due to the hydrophobic properties of porphyrins, and their tendency to aggregate by stacking of the planar molecules they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
124
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 169 publications
(134 citation statements)
references
References 195 publications
0
124
0
1
Order By: Relevance
“…Normally anti-infective agents need to be delivered at a high dosage into the body for an effective treatment. 220 222 However, most of the drug delivery systems have toxicity at their high concentrations. Recently, fluorescent nanomaterials with excellent antibacterial and bacteria targeting functions have been explored.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Normally anti-infective agents need to be delivered at a high dosage into the body for an effective treatment. 220 222 However, most of the drug delivery systems have toxicity at their high concentrations. Recently, fluorescent nanomaterials with excellent antibacterial and bacteria targeting functions have been explored.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Gold nanoparticles (AuNPs) are used in cancer diagnosis and biological imaging because of their excellent optical properties, low cytotoxicity, and good biocompatibility [ 1 , 2 , 3 , 4 , 5 ]. As potential drug carriers, AuNPs have received considerable attention by many researchers [ 6 , 7 , 8 , 9 , 10 ], as it has been frequently reported that they can induce programmed cell death (i.e., apoptosis) [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…They also can be used as a diagnostic gadget and therapeutic "doer". [1][2][3][4] The results from many types of research showed that the specific structural characteristics of these molecules have opened new research fields leading to the design of aptamers. Aptamers are oligonucleotides including ssRNA, ssDNA (single-stranded RNA, DNA) or peptides that bind to select targets with significant dependency and exclusivity due to their specific structural characteristics.…”
Section: Introductionmentioning
confidence: 99%